Prayer wheels - Chou, Yi Ting (2017)
Prayer Wheels is an interactive sound and light installation inspired by Tibetan prayer rituals. The repetitive spinning wheels iterate the Noble Eightfold path - a way to achieve Nirvana. In Prayer Wheels, there are eight similar spinning pods for the visitors to interact with. Each of the created interactive wheels generates unique soundscape and light reactions derived from its spinning movements. The compounded interactions among all the wheels create an immersive light and soundscape.